Is Aid Oil? An Analysis of Whether Africa Can Absorb More Aid. - Collier, P (Elsevier, 2006)
This paper considers whether Africa can absorb a doubling of aid. If oil revenues provide a "natural experiment" the results are disappointing: far from being transformational, they have been markedly less successful than aid. One implication is that the delivery modalities of aid, though heavily criticized, have substantially added value: the paper discusses which modalities may have been most useful. Unfortunately, aid appears to be subject to diminishing returns, so that doubling aid through conventional modalities would not double its impact. The paper concludes by considering innovations in aid modalities, which might offset diminishing returns.